G163 Characteristics of children referred for concerns regarding sexual abuse. (7th April 2014) - Kinross, K; Jaimeson, K; Hodes, D
Abstract : Objectives: To review the characteristics of and clinical findings in children referred to a complex safeguarding clinic. To compare this to findings from other centres and studies. Methods: 225 children were seen over 4 years (November 2009– November 2013) because of historical concerns about possible sexual abuse. Data was analysed retrospectively until Feb 2012 (128 children) and prospectively thereafter (97 children), using a departmental data base, case notes and specific proforma. All descriptions of physical signs and examinations were undertaken in accordance with the guidance from the Royal College of Paediatrics and Child health (The Physcial Signs of Sexual abuse). Prosepective data pending. Results from retrospective data: Of the cohort 25 were boys (all pre-pubertal) and 103 were girls (67 pre, 13 peri and 20 post-pubertal). 61 children were referred due to an allegation made by the child, of which 35 alleged penetration. Ano-genital signs (any): were seen in 24% (30/125) of the cohort, in 32.8% (20/61) reporting any abuse and 42.9% (15/35) reporting penetrative abuse. Anal signs (any): were present in 11.2% of the cohort and Reflex Anal Dilatation (RAD) in 3.2% (all in pre-pubertal girls, 75% of whom had alleged anal penetration). Hymenal notches/transections: were observed in 9% of the cohort, in 17.6% in those with any allegation and 29% alleging penetration. These were seen in peri and post pubertal girls but not in pre-pubertal girls. Signs were more likely to be in the lateral hymenal rim (66.7%) than the posterior (25%) or superior (8.3%) rim. Conclusions: A significant number of children are seen for allegations of CSA. This cohort identified more physical signs than reported in other recent studies of historic abuse. Notches/transections were more common in later puberty, and allegations of penetrative abuse; they were absent in pre-pubertal girls despite a significant number alleging penetration/touching. Anal signs were the most common finding in the pre-pubertal girl. In contrast to other studies, hymenal signs were commonly seen laterally. Physical signs in boys were rare. The significant number of ano-genital signs suggests these persist and examination is an important adjunct when the child alleges historical sexual abuse.